An efficient hybrid strategy for composite yarns of micro-/nano-fibers. (15th December 2019) - Yang, Yuchen; Zhao, Yajie; Quan, Zhenzhen; Zhang, Hongnan; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
Abstract: In contrast to yarns of micro-fibers and those of nano-fibers, composite yarns composed of micro- and nano-fibers exhibit great potential in functional applications by integrating the respective advantages of multiscale fibers. However, the efficient fabrication of composite yarns remains challenging. So far, the existing nano-fiber included yarns, such as nanofiber yarn and core-sheath yarn, exhibit poor durability and low preparation efficiency. Herein, an efficient hybrid strategy for the composite yarns made of multiscale fibers has been developed by integration of electrospun nano-fibers and webbing of micro-fibers. Polyacrylonitrile nano-fiber/viscose micro-fiber composite yarns have been prepared massively. To explore structure of the resulting composite yarns, fluorescent tracer technique was adopted and revealed that nano-fibers are dispersed within composite yarn uniformly, while the structure of composite yarns can be governed easily by adjusting electrospinning parameters. Compared to pure yarns of viscose micro-fibers, the composite yarns possess mechanical properties at the same level, enabling the weaving, knitting and braiding of it for industrial applications. Furthermore, the formation mechanism of the composite yarn has been investigated and the fibrous adhesion among multiscale fibers has been modeled. The efficient approach should be a promising one for the design and scalable fabrication of composite yarns of micro-/nano-fibers. Graphical abstract: Unlabelled Image Highlights: Scalable production of micro-/nano-fiber composite yarns were realized by integrating electrospinning with textile spinning. Structure of the composite yarns was characterized via fluorescent tracer technique. Length of broken nanofibers within composite yarn could be well controlled by adjusting the electrospinning parameters. Formation mechanism of the composite yarn was analyzed and modeled theoretically.